The Next 500 Years: Engineering Life to Reach New Worlds - Mason, Christopher E. (Cambridge, Massachusetts : The MIT Press, 2021)
"Driven by a vision of colonizing other planets, Mason reveals unique insights into how the human body is altered during long-duration spaceflight & how genetic engineering can protect cells in space"--
Includes bibliographical references (pages [259]-266) and index.
Keywords: Space medicine; Astronauts -- Health and hygiene; Astronautics -- Human factors; Genetic engineering